HPLC Determination of Pregabalin in Bulk and Pharmaceutical Dosage Forms After Derivatization with 1-Fluoro-2,4-dinitrobenzene - Souri, E.; Eskandari, M.; Barazandeh Tehrani, M.; Adib, N.; Ahmadkhaniha, R. (Asian Journal of Chemistry, 2013)
Pregabalin is an effective drug used for the treatment of epilepsy, neuropatic pain and anxiety. In this study, a simple and sensitive HPLC method was developed and validated for the determination of pregabalin after derivatization with 1-fluoro-2,4-dinitrobenzene and UV detection at 360 nm. Separation of reaction product was performed on a Nova-Pak C18 column using a mixture of acetonitrile and sodium dihydrogen phosphate 50 mM (pH 2.5) (60:40, v/v) and UV detection at 360 nm. The proposed method showed excellent linearity in the range of 1-100 μg mL-1 (r2 > 0.999). The within-day and between-day precision values were in the range of 0.84-1.98 %. The validated method was successfully used for the determination of pregabalin in the presence of its degradation products under stress degradation, assay preparation of dosage form and dissolution medium without any interference.